2017
DOI: 10.1186/s12986-017-0184-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral β-hydroxybutyrate increases ketonemia, decreases visceral adipocyte volume and improves serum lipid profile in Wistar rats

Abstract: BackgroundKetosis can be induced in humans and in animals by fasting or dietary interventions, such as ketogenic diets. However, the increasing interest on the ketogenic state has motivated the development of alternative approaches to rapidly increase ketonemia using less drastic interventions. Here, it was tested whether oral intake of a β-hydroxybutyrate (βHB) mineral salt mixture could increase ketonemia in Wistar rats without any other dietary changes, thereby being a useful model to study ketones effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 31 publications
4
23
0
1
Order By: Relevance
“…Exogenous ketones drinks are growing in popularity as a method to elevate blood ketone concentrations and mimic a ketogenic diet without the need for dietary changes (Ari et al, 2016 ; Cox et al, 2016 ; Kesl et al, 2016 ; Caminhotto et al, 2017 ; Evans et al, 2017 ). The present study describes the pharmacokinetic and pharmacodynamics properties of ketone ester and salt drinks in humans at rest, and characterizes the effects of a prior meal, which is pertinent to use as a dietary supplement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous ketones drinks are growing in popularity as a method to elevate blood ketone concentrations and mimic a ketogenic diet without the need for dietary changes (Ari et al, 2016 ; Cox et al, 2016 ; Kesl et al, 2016 ; Caminhotto et al, 2017 ; Evans et al, 2017 ). The present study describes the pharmacokinetic and pharmacodynamics properties of ketone ester and salt drinks in humans at rest, and characterizes the effects of a prior meal, which is pertinent to use as a dietary supplement.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to the ketogenic diet is consumption of drinks containing exogenous dietary ketones, such as ketone esters (KE) and ketone salts (KS). The metabolic effects of KS ingestion have been reported in rats (Ari et al, 2016 ; Kesl et al, 2016 ; Caminhotto et al, 2017 ), in three extremely ill pediatric patients (Plecko et al, 2002 ; Van Hove et al, 2003 ; Valayannopoulos et al, 2011 ) and in cyclists (O'Malley et al, 2017 ; Rodger et al, 2017 ). However, the concentrations of blood βHB reached were low (<1 mM) and a high amount of salt, consumed as sodium, potassium and/or calcium βHB, was required to achieve ketosis.…”
Section: Introductionmentioning
confidence: 98%
“…GPR109A was first identified as the receptor responsible for the pharmacological actions of niacin, a lipid-lowering drug in clinical use for more than 40 years [911]. Beta-hydroxybutyrate, identified presently as the only endogenous agonist of the receptor, has too been demonstrated to have some lipid lowering effects [26]. Interestingly, just as some controversy exists regarding whether GPR109A is expressed in liver or not, reports as to whether the lipid-lowering effects of niacin and beta-hydroxybutyrate stem principally from their interaction with the receptor are too conflicting [2730].…”
Section: Discussionmentioning
confidence: 99%
“…BHB was administered in drinking water at a final concentration of 0.01875 g/ml. The BHB dose was estimated using previous studies which showed effective ketosis induction without causing side effects [ 22 , 53 55 ]. The Institutional Animal Care and Use Committee at the University of Wisconsin approved all protocols used in this study.…”
Section: Methodsmentioning
confidence: 99%